PROTEIN-CAPPED GOLD NANOPARTICLES OBTAINED BY A GREEN SYNTHESIS METHOD - COMAN, Cristina; LEOPOLD, Loredana Florina; RUGINĂ, Olivia-Dumitriţa; DIACONEASA, Zoriţa; BOLFĂ, Pompei Florin; LEOPOLD, Nicolae; TOFANĂ, Maria; SOCACIU, Carmen (Studia Universitatis Babeș-Bolyai Chemia, 2015)
A green synthesis protocol for the synthesis of colloidal gold nanoparticles is proposed. The synthesis involves the use of garlic (Allium sativum) extract as reducing agent. The reduction is carried out by slow addition of the Allium sativum extract to the chloroauric acid at boiling and gives spherically shaped nanoparticles, with 10-20 nm size distribution and mean diameters of 15 nm. The gold nanoparticles are characterized by UV-VIS spectroscopy, Fourier Transform Infrared Spectroscopy, Transmission Electron Microscopy, and Surface-Enhanced Raman Scattering. In vitro tests are also performed on human fetal lung fibroblast HFL-1 cells and the nanoparticles are found to be non-cytotoxic for the cells in the concentration range used in our study. Confocal microscopy shows that the particles are localised in the cell cytoplasm.